STUDI REPRODUKSI GENERATIF KERSEN (MUNTINGIA CALABURA) - Oktavita Wulandari; Karmila Fajriah; Muhammad Zulhilmi (Nusadaya Journal of Multidiciplinary Studies, 2025)
Muntingia calabura (kersen) is a tropical plant with high adaptability that reproduces generatively through seeds. This study aimed to determine the generative reproduction process of kersen through natural seed germination and to observe the early growth and adaptive response of the plant after being transplanted into planting media. The method used was observation with a descriptive approach. The study was conducted for approximately 14 days, using young plants resulting from natural germination as the research objects. The procedures included collecting seedlings, transplanting them into planting media, and observing plant growth. The results showed that the plant did not exhibit significant height growth, remaining at approximately 15 cm, and the number of leaves decreased from 8 to 6 due to leaf yellowing and abscission. This condition indicates the occurrence of transplant shock after relocation to new planting media. However, the plant maintained an upright stem, indicating its ability to survive. Therefore, generative reproduction through seeds is the main mechanism of kersen propagation, although early plant growth is strongly influenced by environmental conditions and adaptation processes.